The intriguing relationship between the ABO blood group, cardiovascular disease, and cancer - Franchini, Massimo (BMC Med, 2015)
Other than being present at the surface of red blood cells, the antigens of the ABO blood group system are efficiently expressed by a variety of human cells and tissues. Several studies recently described the involvement of the ABO blood group in the pathogenesis of many human disorders, including cardiovascular disease and cancer, so that its clinical significance extends now beyond the traditional boundaries of transfusion medicine. In a large cohort study recently published in BMC Medicine and including over 50,000 subjects, Etemadi and colleagues reported that nearly 6% of total deaths and as many as 9% of cardiovascular deaths could be attributed to having non-O blood groups, a condition that was also found to be associated with increased risk of gastric cancer. In this commentary, the clinical implications of ABO blood groups are critically discussed and a possible common pathogenic mechanism involving the von Willebrand factor is described. Please see related article http://dx.doi.org/10.1186/s12916-014-0237-8.